Maximum efficiency and power point tracking system for hybrid compensated wireless charging of electric vehicle - Pabba Ramesh; R.K. Pongiannan; Lukas Demel; Roman Hrbac; Narayanamoorthi R (Results in Engineering)
Electric Vehicles (EV) charging using Wireless Power Transfer (WPT) technology has a promising future, however problems with alignment and efficiency optimization still exist. Hybrid compensated WPT systems are proposed in the literature to improve the performance of WPT under misalignment conditions. However, under varied operating conditions, maintaining optimal power transfer efficiency and load power is typically beyond the capabilities of compensatory topologies. Hence, this paper proposes Maximum Efficiency and Power Tracking (MEPT) system for hybrid compensated wireless charging of EVs. In the existing literature, the MEPT systems are proposed for conventional compensated WPT system. Our proposed system involves a MEPT combined hybrid compensation network that dynamically modifies its parameters to attain optimal efficiency and power transfer, thereby circumventing these restrictions. The proposed system monitors the critical parameters like load power, coupling coefficient, and operating frequency and adjusts automatically at the receiver side with simple closed loop control mechanism. Widespread simulation and experimental testing on a 3.3 kW, 85 kHz WPT system are performed to assess the performance of the proposed methodology. Findings show that as compared to conventional compensation approaches, the proposed system increases the power transfer efficiency by 4.67 % with dynamic stability.